DEKONSTRUKSI GENDER DALAM PERSPEKTIF ISLAM - Puji Dwi Darmoko (Yinyang: Jurnal Studi Islam Gender dan Anak, 2012)
Abstract: Gender issue is a globalized one. It queries a lot of things related to inequality between men and women in their relationships, whether the inequality is confirmed by the education, culture, and religion. Moreover, the gender inequality makes gender injustice. Included in Islam, there are many things that are supposed to be gender bias, such as the concept of leadership. Through an analysis of religious texts (the Qur'an and hadith), this paper tries to deconstruct the concept of gender that are considered establish the Islamic society. From here we get a view that Islam is essentially upholds the values of equality and justice between men and women, because they are created from 'one soul' (nafs wahidah). Kata kunci: gender, dekonstruksi, dan Islam